2014
DOI: 10.1111/jpi.12191
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin blunts the mitochondrial/NLRP3 connection and protects against radiation‐induced oral mucositis

Abstract: Mucositis is a common and distressing side effect of chemotherapy or radiotherapy that has potentially severe consequences, and no treatment is available. The purpose of this study was to analyze the molecular pathways involved in the development of oral mucositis and to evaluate whether melatonin can prevent this pathology. The tongue of male Wistar rats was subjected to irradiation (X-ray YXLON Y.Tu 320-D03 irradiator; the animals received a dose of 7.5 Gy/day for 5 days). Rats were treated with 45 mg/day me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
133
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 59 publications
14
133
0
Order By: Relevance
“…In addition, melatonin increases the efficacy of anticancer drugs and has multiple protective effects against drug toxicity [167,168]. The data support the clinical use of melatonin in the co-treatment of cancer.…”
Section: Regulation Of L1 Expressionsupporting
confidence: 52%
“…In addition, melatonin increases the efficacy of anticancer drugs and has multiple protective effects against drug toxicity [167,168]. The data support the clinical use of melatonin in the co-treatment of cancer.…”
Section: Regulation Of L1 Expressionsupporting
confidence: 52%
“…We recently demonstrated that melatonin is synthesized in oral mucosa, where it is involved in autocrine/paracrine signaling by binding to MT1, MT2, and RORγ receptors, thus suggesting that it plays a role in normal oral mucosal physiology [11]. We found that aralkylamine N-acetyltransferase (AANAT) and acetylserotonin O-methyltransferase (ASMT), the two main enzymes in melatonin synthesis, are expressed in oral mucosa and also in salivary glands.…”
Section: A) Melatonin In the Oral Cavitymentioning
confidence: 99%
“…Its important anti-inflammatory effects include expression inhibition of iNOS/i-mtNOS, COX-2 and pro-inflammatory cytokines such as IL-1β or TNF-α. Many of these properties are attributed to the inhibition of NF-κB-dependent innate immune pathway activation [69][70], and we recently showed that melatonin blunts NLRP3 inflammasome activation under different experimental conditions [11,[71][72].…”
Section: Melatonin: a New Treatment For Mucositismentioning
confidence: 99%
See 2 more Smart Citations